Effect of the developmental stage and tissue position on the expression and glycosylation of recombinant glycoprotein GA733-FcK in transgenic plants - Lim, Chae-Yeon; Lee, Kyung Jin; Oh, Doo-Byoung; Ko, Kisung (Frontiers in Plant Science, 2015)
The influence of developmental stage and position (top, middle, and base) of leaves and stem tissues on the expression and glycosylation pattern of a recombinant therapeutic protein -GA733-FcK- was observed in transgenic seedlings during a 16-week growth period. RNA expression gradually increased with age in the middle and basal leaves and decreased in top leaves after 14 weeks. The protein expression level at all leaf positions increased until 14 weeks and slightly decreased at 16 weeks; it was lower in yellow leaves than in green leaves. In stem, protein expression gradually decreased from the top to the base. The glycosylation patterns of GA733-FcK were analyzed from 10 to 16 weeks. The plant-specific glycans increased in the top leaves at 14 weeks, but only slightly changed in the middle and basal leaves. The structure of glycans varied with tissue position. The glycosylation level in the top and middle leaves increased until 12 and 14 weeks, respectively, and decreased thereafter, whereas it decreased in basal leaves until 14 weeks and increased at 16 weeks. In stem, all three sections showed high-mannose type glycan structures. The area size of the glycans was significantly higher in the top stem than in both the middle and basal stems, and it was smaller in yellow leaves than in green leaves. The glycan profiles were similar between green and yellow leaves until 16 weeks. Thus, biomass-harvesting time should be optimized to obtain recombinant therapeutic proteins with ideal glycan structure profiles.